Enhanced Poly(3-hydroxybutyrate) Production from Oil Palm Frond Juice by Cupriavidus necator NCIMB 11599 - Mior Ahmad Khushairi, Mohd Zahari; Hidayah, Ariffin; Mohd Ali, Hassan (2014)
A substantial amount of renewable sugars can be obtained by simply pressing the oil palm frond (OPF) using sugarcane press machine. OPF juice can be utilized as a carbon source for the production of poly(3-hydroxybutyrate), P(3HB) by using a wild type strain of Cupriavidus necator CCUG 52238T.